2009
DOI: 10.1017/s0950268809002039
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological surveillance ofCampylobacter jejuniin chicken, dairy cattle and diarrhoea patients

Abstract: Campylobacter jejuni of different subtypes were identified in chicken, dairy cattle and diarrhoea patients in China from 2005 to 2006, using multiplex PCR and RFLP. The results indicated that, of the three types of samples, C. jejuni was most frequently detected in poultry of the three types of samples, with an average isolation rate of up to 18.61% and a flock contamination rate of 86.67%. The average incidence of C. jejuni in overall cattle and environmental samples, milk cows, heifers and diarrhoea patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 21 publications
(34 reference statements)
0
28
0
3
Order By: Relevance
“…Whether ggt-negative C. jejuni clones are capable to acquire this marker through genetic exchange with ggt-positive clones, thereby promoting its successful colonization in the chicken gut, has yet to be examined. Also, several other studies revealed the presence of identical C. jejuni clones in bovines, chickens, and humans (Nielsen et al 1997, On et al 1998, Gilpin et al 2008, Ragimbeau et al 2008, Huang et al 2009, and even turkeys, sheep, water, dogs, and ostriches (Siemer et al 2004). Recently, it was shown by molecular typing that Campylobacter strains from a broiler house and from an adjacent dairy farm were similar to those subsequently detected in the flock, indicating the importance of horizontal transmission and the risk of transmission of Campylobacter on multispecies farms (Ridley et al 2011).…”
Section: Sources For Horizontal Campylobacter Transmission To Broilermentioning
confidence: 92%
“…Whether ggt-negative C. jejuni clones are capable to acquire this marker through genetic exchange with ggt-positive clones, thereby promoting its successful colonization in the chicken gut, has yet to be examined. Also, several other studies revealed the presence of identical C. jejuni clones in bovines, chickens, and humans (Nielsen et al 1997, On et al 1998, Gilpin et al 2008, Ragimbeau et al 2008, Huang et al 2009, and even turkeys, sheep, water, dogs, and ostriches (Siemer et al 2004). Recently, it was shown by molecular typing that Campylobacter strains from a broiler house and from an adjacent dairy farm were similar to those subsequently detected in the flock, indicating the importance of horizontal transmission and the risk of transmission of Campylobacter on multispecies farms (Ridley et al 2011).…”
Section: Sources For Horizontal Campylobacter Transmission To Broilermentioning
confidence: 92%
“…In addition, the application of bacterial pathogen typing (Ertas et al 2004;Takahashi et al 2006;Wilson et al 2008;Hannon et al 2009;Huang et al 2009;Sheppard et al 2009) and direct detection of host-species specific bacterial DNA (Bernhard & Field 2000b;Dick et al 2005a) could be useful in identifying sources (microbial source tracking; MST) of faecal contamination in surface waters. While library-and culture-independent MST methods are inexpensive, quick, and easy to use (Bernhard & Field 2000b), molecular subtyping methods for pathogens may provide confirmation, and in some cases greater discrimination in the identification of faecal sources of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…ampylobacter jejuni is the major foodborne pathogen that causes human bacterial gastroenteritis (1,2). Chicken is a major reservoir of C. jejuni (3), and contaminated chicken products are recognized as the main source of C. jejuni-related human infections (4).…”
mentioning
confidence: 99%